PENGARUH PROKRASTINASI AKADEMIK DAN DUKUNGAN SOSIAL KELUARGA TERHADAP STRES SISWA KELAS XII MIPA - Farah Wahidayati, Talenta; Wibawanti, Inayah (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
Academic stress is the pressure experienced by students due to academic demands, which can affecttheir mental health and learning performance. This study aims to determine the influence ofacademic procrastination and family social support on academic stress among 12th-grade sciencestudents. This research uses a quantitative approach with a correlational design. The samplingtechnique employed simple random sampling with a total sample of 92 students. The researchinstruments used were Likert scales to measure levels of academic stress, academic procrastination,and family social support. Data were analyzed using T-tests, ANOVA, and classical assumption tests.The results showed that academic procrastination has a positive and significant effect on academicstress (t = 15.199, P < 0.001), while family social support has a negative and significant effect onacademic stress (t = -3.671, P < 0.001). The ANOVA test indicated that both variables together havea significant effect on academic stress (F = 116.610, P < 0.000). Thus, academic procrastinationincreases academic stress, while family social support reduces academic stress among 12th-gradescience students.